Anti-Radicalism Islamic Education Strategy in Islamic Boarding Schools - Gunawan Widjaja; Sanchita Bhattacharya; Muhammad Anas Ma`arif; Aslan Aslan (Program Pascasarjana Universitas Ibrahimy, 2022)
This article describes the anti-radicalism education management strategy at the Amanatul Ummah Islamic boarding school (Pesantren), Mojokerto. This article uses a type of qualitative research with a case study approach. The subject of this research is the Pondok Pesantren Amanatul Ummah Pacet Mojokerto. Informants from this study were teachers at Islamic boarding schools, foundation managers, and Islamic boarding school education staff. This article results in (1) The Amanatul Ummah Islamic Boarding School Education Planning is carried out once a year. As for the planning of anti-radicalism education, in particular, they selected teachers who understand NU Aswaja—strengthening the curriculum with the value of religious moderation. (2) Strengthening the curriculum in applying anti-radicalism education in Islamic boarding schools by providing an understanding of the Aswaja NU tradition. Discipline applies the NU tradition in all Islamic boarding school activities. The following recommendation is to research the aspects of moderation-based pesantren leadership patterns.